84% efficiency improvement in all-inorganic perovskite light-emitting diodes assisted by a phosphorescent material. Issue 28 (26th April 2018) - Gao, Chun-Hong; Ma, Xing-Juan; Zhang, Yue; Yu, Fu-Xing; Xiong, Zi-Yang; Wang, Zhi-Qiang; Wang, Run; Jia, Ya-Lan; Zhou, Dong-Ying; Xiong, Zu-Hong
Abstract : Remarkable EL performance is achieved in CsPbBr3 :FIrpic perovskite light-emitting diodes assisted by a phosphorescent material. Abstract : A novel mixed perovskite emitter layer is applied to design all-inorganic cesium lead halide perovskite light-emitting diodes (PeLEDs) with high electroluminescence (EL) performance, by combining CsPbBr3 with iridium(iii )bis[2-(4′, 6′-difluorophenyl)pyridinato-N, C 2 ′]-picolinate (FIrpic), where FIrpic is a phosphorescent material with very high internal quantum efficiency (IQE) approaching 100%. The CsPbBr3 :FIrpic PeLEDs show a maximum luminance of 5486 cd m −2, and an external quantum efficiency of 0.47%, which are 1.84 and 1.76 times that of neat CsPbBr3 PeLEDs, respectively. It is found that FIrpic molecules as an assistant dopant can efficiently transmit energy from the excitons of FIrpic to the excited state of the CsPbBr3 emitter via a Förster energy transfer process, leading to enhanced EL efficiency in the CsPbBr3 :FIrpic PeLEDs.